2017
DOI: 10.1017/ice.2017.244
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of MRSA ST398 Carriage in Nursing Home Residents in an Area of Spain With a High Density of Pig Farming

Abstract: MRSA nasal carriage was detected in 15.7% of 204 residents from 6 nursing homes (NHs) in the Osona region (Barcelona, Spain), and the MRSA-ST398 lineage was identified in 15.6% of MRSA-positive residents and in 2.5% of all NH residents evaluated. Most MRSA-ST398 carriers (4 of 5) had direct or indirect contact with pig farms. Infect Control Hosp Epidemiol 2018;39:90-93.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The MRSA prevalence rate in our area has remained practically the same (25.8%) as a similar study carried out by our research group in 2014 [14]. In the literature, the prevalence of MRSA in LTCFs exhibits significant variability worldwide, showing large geographical differences [2,[15][16][17][18][19][20][21][22][23]. The highest prevalence has been reported in studies from Asia, some of them reaching a rate of 65% [24,25].…”
Section: Discussionsupporting
confidence: 75%
“…The MRSA prevalence rate in our area has remained practically the same (25.8%) as a similar study carried out by our research group in 2014 [14]. In the literature, the prevalence of MRSA in LTCFs exhibits significant variability worldwide, showing large geographical differences [2,[15][16][17][18][19][20][21][22][23]. The highest prevalence has been reported in studies from Asia, some of them reaching a rate of 65% [24,25].…”
Section: Discussionsupporting
confidence: 75%
“…[9][10][11][12][13][14] Studies from around the world have reported a wide-ranging prevalence of MRSA colonization among LTCF residents of 4-65%. [14][15][16][17][18][19][20][21][22][23][24] This prevalence is much higher than that of the general population, as well as that in hospital settings, [25][26][27][28][29] leading to the conclusion that geriatric LTCFs are potential reservoirs for MRSA. [24,[29][30][31][32][33][34][35] Several studies using genotyping methods have previously indicated that MRSA is most likely imported from hospitals into LTCFs via the transfer of patients, [35][36][37][38] which might be associated with the high prevalence of MRSA colonization among LTCF residents.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the prevalence of CC97 in recent years in Kuwait may suggest an increased transmission among patients in hospitals. CC97 has also been sporadically reported in patients in Saudi Arabia (Monecke et al, 2012), Spain (Lozano et al, 2011;Reynaga et al, 2018), and Australia (Monecke et al, 2011). Although CC97 is rarely reported in humans (Grundmann et al, 2010;Schaumburg et al, 2012), it is commonly isolated from cattle, and it is considered one of the most common causes of bovine mastitis (Smith et al, 2005;Aires-de-Sousa et al, 2007;Sung et al, 2008) and one of the most common in the Italian pig industry (Battisti et al, 2010;Feltrin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%